Buoyancy induced heat transfer deterioration in vertical concentric and eccentric annuli - Forooghi, P.; Abdi, I.A.; Dahari, M.; Hooman, K. (Elsevier, 2015)
Turbulent convection heat transfer of upward fluid flows in vertical annular channels with uniformly heated inner wall and adiabatic outer wall is investigated numerically. Two concentric geometries with outer-to-inner diameter ratios of 2.4 and 3 as well as two eccentric geometries with identical outer-toinner diameter ratio of 2.4 and eccentricities of 0.25 and 0.5 are investigated. Heat transfer deterioration, similar to that of a circular pipe, is observed. The range of buoyancy parameter, over which deterioration is observed, is close to that of circular pipes. Moreover, it is observed that when the value of eccentricity increases, the deterioration phenomenon becomes less pronounced and recovery of heat transfer coefficient occurs earlier, i.e. at lower buoyancy parameters compared to concentric annuli. (C) 2014 Elsevier Ltd. All rights reserved.